Insuppressible cognitions in the reflexive imagery task: Insights and future directions - Yankulova, Jessica K.; Zacher, Lisa Moreno; Velasquez, Anthony G.; Dou, Wei; Morsella, Ezequiel (Frontiers in Psychology, 2022)
In 1959, Neal Miller made the bold claim that the Stimulus-Response, Behaviorist models of that era were describing the way in which stimuli lead to the entry of contents into consciousness (“entry,” for short). Today, researchers have begun to investigate the link between external stimuli and involuntary entry, using paradigms such as the reflexive imagery task (RIT), the focus of our review. The RIT has revealed that stimuli can elicit insuppressible entry of high-level cognitions. Knowledge of the boundary conditions of the RIT effect illuminates the limitations of involuntary processes and the role of consciousness in the regulation of behavior. We review the boundary conditions of this paradigm as well as its systematic effects. Systematic effects are unlikely to be due to experimental demand. While reviewing each effect, we consider its theoretical implications. In addition, throughout our review, we discuss future directions for the study of insuppressible entry using the RIT. Last, we discuss a theoretical development (passive frame theory) that stems from the RIT and illuminates how involuntary entry and encapsulation, though at times disadvantageous for the actor, is essential for adaptive action selection during the course of ontogeny.